Identification of potent orally active factor Xa inhibitors based on conjugation strategy and application of predictable fragment recommender system. Issue 2 (15th January 2015) - Ishihara, Tsukasa; Koga, Yuji; Iwatsuki, Yoshiyuki; Hirayama, Fukushi
Graphical abstract